Preeclampsia and subsequent risk of cancer: update from the Jerusalem Perinatal Study - CALDERON-MARGALIT, R. (2008)
OBJECTIVES: To study the association between preeclampsia and cancer incidence. STUDY DESIGN: The Jerusalem Perinatal Study is a population-based cohort of all births to 41,206 residents of Western Jerusalem in 1964-76. Cancer incidence to 2004 was assessed by linkage of the cohort with the Israel Cancer Registry. Cox’s proportional hazards models were constructed to estimate the hazard ratio (HR) for cancer among women who had had preeclampsia. RESULTS: Preeclampsia was associated with a 1.23-fold increased risk of cancer at all sites, a 37% increased risk of breast cancer, and more than a doubling of ovarian cancer risk. Analysis by morphology yielded significantly increased risks for malignancies classed as cystic mucinous and serous (RR:1.96, 95% Confidence interval:1.00-3.83), and for ductal, lobular and medullary carcinomas (1.40, 1.07-1.83). No differential association was observed by sex of offspring. CONCLUSIONS: Our study suggests that the previously-described protective effect of preeclampsia on cancer is not universal.